Terjemahan Istilah Biologi dalam Biologi Edisi Kedelapan Jilid 1 - Yenny Chusna Khustina; Haru Deliana Dewi (Madah: Jurnal Bahasa dan Sastra, 2022)
This study focuses on the translation procedures of biological terms in the “Sel” chapter in Biologi Edisi Kedelapan Jilid 1 and compares which procedures are the most precise in delivering meanings. The precision was analyzed based on the standard spelling using online KBBI; the conformance to the adopted word’s element writing rules using PUEBI (2016); and/or the componential analysis of meaning by Nida (1975). 10 translation procedures were used to translate 530 biological terms, i.e., in descending order, phonological translation, literal translation, transference, couplets or triplets, transposition, contextual conditioning, generalization, addition, descriptive translation, and particularization. Phonological translation was the most used as the terms were mostly cell parts, biochemical compounds, enzymes, biological processes, and biochemical processes. Literal translation, couplets or triplets, and generalization were more prone to causing imprecision with fatal consequences, while phonological translation and transference were not. In addition, 5 tendencies were found in the translation of the suffixes in biological terms, and special rules are necessary to regulate them.